A PRE-TEST LOGO AND ADVERTISING “MARI KEMBALI KE DESA” SOCIAL CAMPAIGN TO MOTIVATE FIRST JOBBERS WANDERERS IN JAKARTA - Vashti Trisawati Abhidana; Novi Dila Kana (Bina Nusantara University, 2019)
Urbanization in Indonesia brings a complex problem in the cities. People from the rural area perceive big city will bring more prosperity than living in their village. However, some young adults who lived in the urban area because of their work, think about to groom and grow their own village to make the community alive and make some changes. Therefore, through the social campaign “Ayo Kembali Ke Desa” created by one of the graphic design new media students (GDNM), is motivating young adults to go back to the village. In this paper is conducting a pretest for campaign logo and promotional materials that has been created, because in social campaign conducting a pre-test test is a mandatory before launching the campaign. To test the logo and advertisement materials, the researchers use the approach of Seven Steps Paul Rand Logo test and Ten Elements of Advertisement Test. Through qualitative research with focus group discussion, the campaign has good prospect gain the interest of the target audience with several adjustments, especially in logo and series of print advertisements; however, for TV commercial the visual needs more emotional approach scenes.